Nanoengineering of Phosphate/Phosphonate Drugs via Competitive Replacement with Metal‐Phenolic Networks to Overcome Breast Tumor with Lung and Bone Metastasis - Wanrui Shi; Dashuai Liu; Wenjie Feng; Yang Chen; Yonggang Wang; Zhihong Nie; Yi Liu; Hao Zhang (Advanced Science)
Abstract Phosphate and phosphonate drugs are vital in building organisms, regulating physiological processes, and exhibiting diverse biological activities, including antiviral, antibacterial, antineoplastic, and enzyme‐inhibitory effects. However, their therapeutic potential is limited by the lack of advanced nanoengineering technologies. Herein, a competitive coordination strategy for nanoengineering phosphate/phosphonate drugs is introduced. By leveraging the difference in coordination capabilities between polyphenols and phosphates/phosphonates with metal ions, various phosphate/phosphonate‐based nanodrugs using metal‐phenolic networks (MPNs) as templates and phosphate/phosphonate drugs as competitive agents are constructed. The dynamic nature of these coordination bonds imparts stimuli‐responsiveness to the nanodrugs, allowing for targeted release and therapy. As a proof of concept, Fe3+ and galangin are used to form the MPN template, zoledronic acid and cGAMP as competitive agents, and DOX as the loaded drug to construct DOX@Fe‐galangin@Fe‐zoledronic acid‐cGAMP nanodrugs. The results demonstrate that, by triggering pyroptosis and activating the cGAS‐STING pathway, the nanodrugs exhibit potent cytotoxicity and accurate selectivity in eradicating orthotopic breast tumors, and activate an antitumor immune response against lung and bone metastases. Because the competitive coordination strategy is applicable to a variety of phosphate/phosphonate agents, it holds significant potential for enhancing the clinical efficacy of phosphate/phosphonate drugs and advancing nanodrug development for complex therapeutic applications.